The prostaglandin EP1 receptor potentiates kainate receptor activation via a protein kinase C pathway and exacerbates status epilepticus - Rojas, Asheebo; Gueorguieva, Paoula; Lelutiu, Nadia; Quan, Yi; Shaw, Renee; Dingledine, Raymond (Neurobiology of disease, 2014)
Prostaglandin E2 (PGE2) regulates membrane excitability, synaptic transmission, plasticity, and neuronal survival. The consequences of PGE2 release following seizures has been the subject of much study. Here we demonstrate that the prostaglandin E2 receptor 1 (EP1, or Ptger1) modulates native kainate receptors, a family of ionotropic glutamate receptors widely expressed throughout the central nervous system. Global ablation of the EP1 gene in mice (EP1-KO) had no effect on seizure threshold after kainate injection but reduced the likelihood to enter status epilepticus. EP1-KO mice that did experience typical status epilepticus had reduced hippocampal neurodegeneration and a blunted inflammatory response. Further studies with native prostanoid and kainate receptors in cultured cortical neurons, as well as with recombinant prostanoid and kainate receptors expressed in Xenopus oocytes, demonstrated that EP1 receptor activation potentiates heteromeric but not homomeric kainate receptors via a second messenger cascade involving phospholipase C, calcium and protein kinase C. Three critical GluK5 C-terminal serines underlie the potentiation of the GluK2/GluK5 receptor by EP1 activation. Taken together, these results indicate that EP1 receptor activation during seizures, through a protein kinase C pathway, increases the probability of kainic acid induced status epilepticus, and independently promotes hippocampal neurodegeneration and a broad inflammatory response. •Mice lacking EP1 displayed a reduced likelihood to enter status epilepticus.•EP1 receptor lacking mice had decreased hippocampal neurodegeneration.•EP1 receptor lacking mice showed a blunted inflammatory response.•Native and recombinant kainate receptors are potentiated by EP1 activation.•PKC acting on residues in GluK5 underlie kainate receptor potentiation by EP1.